Stress corrosion cracking of tube of a vaccum residue steam generator: a case study - Shaban, H. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Causes of failure of a vacuum residue steam generator tubes were investigated using visual, microscopic and chemical methods. It was found that the main cause of such failure was due to stress corrosion cracking. Suggestions were made to control causes of such failure.